ANALYSIS OF THE CURRENT STATE OF TAXATION OF COMMERCIAL BANKS’ PROFITS IN UZBEKISTAN (World Bulletin of Social Sciences, 2024)
The article analyzes the current state of taxation of commercial banks’ profits in Uzbekistan, reviews the practice of taxation in legislation, as well as provides a comparative analysis of standard profit tax rates for commercial banks. In reliance upon the research results the author has developed relevant conclusions and proposals.